Determine os zeros da função f(x) = 2x2 – 2x + 6.
Soluções para a tarefa
Respondido por
0
- Iguale a zero e resolva.
2x² - 2x + 6 = 0
x² - x + 3 = 0
x² - x = - 3
x² - x + 1/4 = - 3 + 1 /4
(x - 1/2)² = - 11/4
(x - 1/2)² = - 11/2²
x - 1/2 = ± √(- 11)/2
x = 1/2 ± i√11/2
x = (1 ± i√11)/2
Resposta: (1 ± i√11)/2
Usuário anônimo:
V11.i
Respondido por
0
Explicação passo-a-passo:
Como , essa função não possui zeros reais.
Perguntas interessantes
Biologia,
9 meses atrás
História,
9 meses atrás
Informática,
9 meses atrás
Artes,
11 meses atrás
Matemática,
11 meses atrás
Sociologia,
1 ano atrás